2019
DOI: 10.1007/978-3-030-15719-7_22
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Edge Embedding for Friend Recommendation

Abstract: We propose a friend recommendation system (an application of link prediction) using edge embedding on social networks. Most real world social networks are multi-graphs, where different kinds of relationships (e.g., chat, friendship) are possible between a pair of users. Existing network embedding techniques do not leverage signals from different edge types and thus perform inadequately on link prediction in such networks. We propose a method to mine network representation that effectively exploits edge heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Pointwise learning models transfer the sorting problem into a multi-classification problem or a regression problem [11], [12], and the disadvantage is that these models cannot deal with the high skewness of data very well. Pairwise learning models treat friend recommendation as a learning to rank problem based upon pairwise comparisons [14], [19], [24]- [26], [43]. Such kind of approaches can better overcome the problem of data skewness, but often suffers the problem of too large training dataset size and high time complexity.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Pointwise learning models transfer the sorting problem into a multi-classification problem or a regression problem [11], [12], and the disadvantage is that these models cannot deal with the high skewness of data very well. Pairwise learning models treat friend recommendation as a learning to rank problem based upon pairwise comparisons [14], [19], [24]- [26], [43]. Such kind of approaches can better overcome the problem of data skewness, but often suffers the problem of too large training dataset size and high time complexity.…”
Section: Related Workmentioning
confidence: 99%
“…It can model different objects and their rich relations in RSs, in which objects are of different types and links among objects represent different relations. HINbased recommendation model can better overcome the data sparsity problem because of the ability to integrate abundant information into the model [19], [27]- [29].…”
Section: Related Workmentioning
confidence: 99%
“…Most of the research work has been focused on the extraction of information from the network by making network specific assumptions. These traditional mechanisms perform well on the specific networks while they fail miserably on the networks in which the assumptions do not hold true [8]. There are techniques like node embedding that encode the nodes present in the network into low dimensional vectors.…”
Section: Related Workmentioning
confidence: 99%
“…There has been a lot of research in Link Prediction. Most of the work is focused on exploiting structural information using hand engineered features in which specific aspects and assumptions are taken into consideration [8]. Most of the work in link prediction revolves around exploiting the structure of the network in order to compute features based on various assumptions about the given network and predicting links based on those features.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2, the initialization of shared node embedding could be random or pre-defined. Since the experiment results of [44] suggested that Node2Vec is more efficient than DeepWalk as the node initialization of their edge embedding model, we adopt Node2Vec as the pre-defined node initialization method and investigate if it's beneficial to MERL. Table 4 shows that the MERL variants with Node2Vec initialization outperform other variants without Node2Vec initialization.…”
Section: Conversation Factorsmentioning
confidence: 99%